Patenting antibody combination therapies. (3rd December 2020) - Feng, Li; Chen, Lin; Murphy, Amanda; Jacobstein, Jeffrey; Lewis, Stacy
Abstract: There is emerging, intense interest in antibody combination therapies. However, antibody combination therapies pose unique intellectual property challenges. In some instances, it may be difficult to obtain patents with claims that provide innovators with adequate protection for such inventions. Patent examiners often regard claims to a composition or use of an antibody in combination with another therapeutic agent as obvious if the individual components of the combination were both known and well-studied in the field for use in treating similar indications. Nevertheless, even if the individual components of a combination were known and generally effective, the combination therapy may not be obvious if there would not have been a motivation to specifically combine the individual components or if there was no reasonable expectation of success in combining the components. Antibody combination therapies may also offer fertile grounds for demonstrating objective evidence of nonobviousness for a particular combination, such as through unexpected results, if a sufficient nexus can be established across the scope of the claims and if the superior results constitute a significant improvement.